Analisis Faktor-Faktor yang Mempengaruhi Profabilitas(ROI) Pada Perusahaan Barang Konsumsi - Siti Aisyah Nasution; Peronita Lestari; Whitny Tanisha; Erika Stevani Br Sembiring (Politeknik Ganesha Medan, 2022)
The purpose of this research is to determine the effect of sales, operating cost, cash turnover, and inventory turnover on the return on investment (ROI) of consumer goods companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research uses a quantitative descriptive presentation with a total sample of 29 consumer goods companies. The sample selection using data collection techniques used in this research is literature study and official sources of data, in this case published by the Indonesia Stock Exchange on its website www.idx.co.id . Hypothesis testing of the data is tested using the classical assumption test. The value of Adjusted Rsquare is 0.203, which means 20.3% and the other independent variables are 79.7%. The results of the discussion separately state that Sales, Operating Costs, and Cash Turnover have an effect but Inventory Turnover has no effect on Return On Investment. Sales, Operational Costs, Cash Turnover and Inventory Turnover as a whole have an influence on Return On Investment.